BUEN VIVIR IN ECUADOR: HAS THE CONSTITUTIONAL PRINCIPLE BEEN REFLECTED IN STRUCTURAL CHANGE FOR DEVELOPMENT? - Vaz Oliveira Aguiar, Rodolfo; Fróes de Borja Reis, Cristina (Brazilian Keynesian Review, 2023)
This paper aims to investigate the economic dynamics between 2007 and 2017 in Ecuador considering the adoption — as a constitutional principle — of an ecological ideal, which emerged from the indigenous peoples of Latin America: Buen Vivir. The historical process that enshrined this concept made the Ecuadorian experience stand out in the recent history of South America. Economic planning was defined as a fundamental dimension to diversifying the productive structure. However, the dependence on oil extraction represented major obstacles to Buen Vivir, since its funding was based on fiscal policies enabled by resources from a non-sustainable activity. We analyze this process based on a theoretical background from Latin-American structuralism to Buen Vivir, examining the Ecuadorian economic plans and actual dynamics during Rafael Correa’s administration, considering the following relevant macroeconomic variables: industrial composition of value-added, exports profile, public investment, foreign direct investment, energetic matrix, and structure of employment. The conclusion is that the evolution of the Ecuadorian economy has not allowed for development strictly according to the parameters of Buen Vivir.